Prolegómenos para entender la regulación de la calidad en la ens eñanza universitaria - Chang Chuyes, Guíllermo (Revista de Derecho, 2019)
This work wants to establish the bases to understand the quality and its application to the universities. Therefore, in a first part we analyze the term quality, to discover its meaning. Then it is exposed how the companies and the State look for the quality in its activities, and how the State tries to regulate it. In the second part, we analyze the structure of the university in Peruvian law, how its quality should be and if the state can regulate it.